2010
DOI: 10.1186/1471-2180-10-42
|View full text |Cite
|
Sign up to set email alerts
|

The cell envelope subtilisin-like proteinase is a virulence determinant for Streptococcus suis

Abstract: BackgroundStreptococcus suis is a major swine pathogen and zoonotic agent that mainly causes septicemia, meningitis, and endocarditis. It has recently been suggested that proteinases produced by S. suis (serotype 2) are potential virulence determinants. In the present study, we screened a S. suis mutant library created by the insertion of Tn917 transposon in order to isolate a mutant deficient in a cell surface proteinase. We characterized the gene and assessed the proteinase for its potential as a virulence f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
49
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 37 publications
(48 reference statements)
2
49
0
Order By: Relevance
“…We used a well-established intraperitoneal mouse infection model (4,9,50) to assess virulence of the ⌬troA mutant. This demonstrated that TroA is required to cause systemic disease in mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We used a well-established intraperitoneal mouse infection model (4,9,50) to assess virulence of the ⌬troA mutant. This demonstrated that TroA is required to cause systemic disease in mice.…”
Section: Discussionmentioning
confidence: 99%
“…To test the virulence of the ⌬troA mutant bacteria in systemic infection, we used a murine infection model broadly used to assess virulence of S. suis mutants (4,9,50). Ten CD1 mice were inoculated intraperitoneally with 10 9 CFU of wild-type or ⌬troA mutant bacteria.…”
mentioning
confidence: 99%
“…sspA encodes a surface-associated subtilisin-like protease, which is capable of degrading IL-8, a major chemo-attractant of neutrophils . Deletion of sspA attenuated SS virulence in a mouse model and was more susceptible to killing by whole blood than the wild-type strain P1/7 (Bonifait et al 2010). This could be a potential way through which rss03 contributes to the survival of SS in blood.…”
Section: Ss Srnas Contribute To Bacterial Survival In Pig Bloodmentioning
confidence: 99%
“…Overall, the cps locus in the JS14 genome showed strong similarity to that in serotype 1 strain identified earlier, which may explain why serotype-specific PCR method could not differentiate serotype 1 and serotype 14 (18). CDSs for a few virulence-associated factors, such as suilysin, extracellular protein factor, fibronectin/fibrinogen-binding protein (6), serum opacity-like factor (1), sortase A (15,19,20), peptidoglycan GlcNAc deacetylase (8), D-alanylated lipoteichoic acid (9), and subtilisin-like serine protease (3,4,12), which were confirmed to contribute to the virulence of serotype 2, were also found in the genome of JS14. Learning more about these factors would strengthen our understanding on the virulence of S. suis serotype 14.…”
mentioning
confidence: 99%